FILOSOFI SUNAN GUNUNG JATI â€œINGSUN TITIP TAJUG LAN FAKIR MISKINâ€ SEBAGAI UPAYA PENGENTASAN KEMISKINAN DI KOTA CIREBON DALAM TELAAH TEORI CULTURE POVERTY - Alfian Febriyanto (JURNAL YAQZHAN: Analisis Filsafat, Agama dan Kemanusiaan, 2023)
ABSTRACT: This article discusses the philosophy of Sunan Gunung Jati " ingsun titip tajug lan fakir miskin" as an effort to alleviate poverty in Cirebon City in a culture poverty theory study. The purpose of this study is to present a new view that comes from culture poverty theory in poverty alleviation efforts in Cirebon. Thus the formulation of the problem in this paper is how culture poverty theory views Sunan Gunung Jati's philosophy "Ingsun entrusts tajug and the poor" in poverty alleviation efforts in Cirebon. This study uses a qualitative descriptive method. The theoretical framework used is culture poverty theory. The results of the research show that culture poverty theory sees social reality as full of inequality and injustice. The development of capitalism resulted in the polarization of social classes in society. This social class polarization occurs due to the concentration of wealth in one part of the social class and the concentration of poverty in another. So far, poverty alleviation carried out by the private sector is often carried out through corporate social responsibility (CSR) programs. It's just often just a formality only. The government is obliged to prosper all citizens. The private sector is responsible for alleviating poverty in the vicinity of the industrial location. People who are classified as poor also have a responsibility to get out of this condition immediately